Fostering Brave Spaces for Discussions About Race - Grace I Gilmour (Middle Grades Review, 2021)
The persistence of the ideology of white supremacy requires a deep understanding of race and racism in order to dismantle inequitable systems in the United States. White students in particular do not have the knowledge or tools to understand our racialized society. Education is a powerful means to either interrupt or perpetuate systems of oppression. Not only is it the responsibility of schools to interrupt, but young adolescents are developmentally ready to engage in nuanced and potentially difficult conversations about social identity and justice. Teachers need to work with their students to thoughtfully build brave classroom communities to sustain these conversations. This work should look different depending on the demographic makeup of a classroom. This practitioner's perspective will propose antiracist curricular and pedagogical approaches for a majority-white school environment.
Keywords: middle level education; social justice; antiracism; whiteness; social identity; curriculum